Turning Point Processes to Higher Education among Care Leavers - Tehila Refaeli (Social Work and Society, 2014)
Children who grew up in care institutions encounter many difficulties in the years after leaving care, including challenges related to their low education achievements while they were still in care. Higher education is therefore hard and sometimes almost impossible to achieve. The current article uses data from a research project which focuses on the experiences of care leavers who have made their way into higher education. In the current article we present findings related to the concept of turning points, as representing positive change in the life course of young people. We hypothesized that we could find turning points in the life stories of the few care leavers who have become engaged in higher education. To this end, we present two case studies of care leavers and analyze these for possible turning points in their life stories. Out of the auto-biographical interviews, we analyzed turning points which include different aspects: a significant event is happening and creates an opportunity for change in the life course. This opportunity is connected to a biographical learning process of the person himself, but is additionally accompanied and prepared with the help of significant others. Finally, ongoing personal support after the opportunity and biographical learning process seems to be important to create a turning point as a lasting change. Because of its process-based nature (instead of the idea of a single significant event), we name the identified change a turning point process.